ANALISIS RISIKO KESEHATAN LINGKUNGAN PAJANAN GAS HIDROGEN SULFIDA (H2S) PADA PEMULUNG AKIBAT TIMBULAN SAMPAH DI TPA JATIBARANG KOTA SEMARANG - Bariyadi Rifai; Tri Joko; Yusniar Hanani Darundiati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Garbage decomposition process at landfill causes air pollution, one of which is hydrogen sulfide gas that is colorless ,highly toxic ,flammable and has a characteristic smell of rotten eggs. H2S gas can cause health problems,especially in the respiratory tract. The scavengers rarely wear masks while working in Jatibarang landfill. This study was done to analyze the environmental health risk assessment of H2Sgas to scavengers at Jatibarang landfill. This research is a cross-sectional research with Environmental Health Risk Analysis (ARKL) method. The sample in this study is male scavengers and settled in the landfill more than one year amounted to 65 people. The results of the measurement of H2S gas concentrations in Jatibarang landfill with an average of 0.0057 ppm is below the threshold value. Projection exposure to real time, scavengers at the landfill Jatibarang do not have the risk of noncarcinogenic RQ (0.67 <1). Exposure projection for the next 5 years in there will cause a health risk noncarcinogenic (RQ> 1). In the calculation of individual scavengers found that 12.3% (8 people) scavengers already occurred non-carcinogenic risk (RQ> 1). Health complaints experienced by scavengers such as a headache, dizziness, irritation and pain in the respiratory tract.The conclusion of this study is the population of scavengers at the Jatibarang landfill doesnot have non-carcinogenic health risks. Scavengers will have a noncarcinogenic risk for about 10.43 years exposureduration (Dt) or in their next 3.43 years.